2016
DOI: 10.1002/jcb.25676
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Induces Reactive Oxygen Species Through a Membrane Glucocorticoid Receptor in Rainbow Trout Myotubes

Abstract: Cortisol is an essential regulator of neuroendocrine stress responses in teleosts. Cortisol predominantly affects target tissues through the genomic pathway, which involves interacting with cytoplasmic glucocorticoid receptors, and thereby, modulating stress-response gene expressions. Cortisol also produces rapid effects via non-genomic pathways, which do not involve gene transcription. Although cortisol-mediated genomic pathways are well documented in teleosts, non-genomic pathways are not fully understood. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 36 publications
4
27
0
Order By: Relevance
“…Studies in Merino sheep showed that the initiation and maturation of secondary follicles during fetal life and early postnatal period were inhibited by malnutrition, this may be attributed to the reactive oxygen species (ROS) production and oxidative stress induced by malnutrition . In addition, studies on Merino sheep showed that secondary follicle development during fetal and early postnatal period under normal conditions was suppressed by plasma cortisol, a stress‐related hormone that was reported to induce ROS production and oxidative stress …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Merino sheep showed that the initiation and maturation of secondary follicles during fetal life and early postnatal period were inhibited by malnutrition, this may be attributed to the reactive oxygen species (ROS) production and oxidative stress induced by malnutrition . In addition, studies on Merino sheep showed that secondary follicle development during fetal and early postnatal period under normal conditions was suppressed by plasma cortisol, a stress‐related hormone that was reported to induce ROS production and oxidative stress …”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] In addition, studies on Merino sheep showed that secondary follicle development during fetal and early postnatal period under normal conditions was suppressed by plasma cortisol, 17,18,26,27 a stress-related hormone that was reported to induce ROS production and oxidative stress. 28,29 Development of secondary follicles involves complex epithelium-mesenchyme interactions between follicular epithelial keratinocytes and underlying mesenchymal cells in the dermis 30,31 and depends on a delicate balance between cell proliferation and apoptosis. 32,33 Excessive ROS generation causes damage to all cellular components including proteins, lipids, and DNA and triggers apoptosis of mesenchymal stem cells (MSCs) and epithelial stem cells that are the progenitors of secondary hair follicle cells.…”
mentioning
confidence: 99%
“…In fish models, the non-genomic cortisol actions have been associated with the suppression of phagocytosis in the freshwater teleost Channa punctatus (17) and with the increased plasma membrane fluidity and activation of protein kinase cAMP-dependent (PKA), protein kinase B (PKB), and protein kinase C (PKC) signaling pathways in rainbow trout hepatocytes (20, 21). In addition, this cortisol action also induces the extracellular signal-regulated kinase (ERK)—cAMP-responsive element binding protein (CREB) signaling pathways activation and the up regulation of peroxisome proliferator-activated receptor γ co-activator 1 α ( pgc1a) expression in isolated rainbow trout myotubes (22). Even though, the mechanisms involved in the non-genomic cortisol pathways are complex and diverses, the impact in the adaptive response in fish are far from clear (23).…”
Section: Introductionmentioning
confidence: 99%
“…Cortisol action on target tissues includes activation of the intracellular glucocorticoid receptor (GR) and/or the mineralocorticoid receptor (MR) as ligand‐bound transcription factors which are ubiquitously expressed (Faught, Aluru, & Vijayan, ; Mommsen et al., ; Stolte, Verburg van Kemenade, Savelkoul, & Flik, ). Recent work has also implicated the possibility of nongenomic and rapid cortisol signalling in fish tissues, including pituitary (Borski, Hyde, & Fruchtman, ), liver (Dindia, Faught, Leonenko, Thomas, & Vijayan, ; Dindia et al., ), gill and brain (Sunny, Lakshmy, & Oommen, ) and myotubes (Espinoza et al., ). While the primary role of cortisol during stress is energy repartitioning to metabolically allow the animals to cope with stressor insult (Pankhurst, ), the effect on reproduction is generally considered inhibitory (Pankhurst, ; Pankhurst & Van Der Kraak, ; Schreck et al., ).…”
Section: Introductionmentioning
confidence: 99%